Targeting Nanotechnology and Nutraceuticals in Obesity: An Updated Approach - Sharma, Neelam; Behl, Tapan; Singh, Sukhbir; Kaur, Parneet; Zahoor, Ishrat; Mohan, Syam; Rachamalla, Mahesh; Dailah, Hamed G.; Almoshari, Yosif; Salawi, Ahmad; Alshamrani, Meshal; Aleya, Lotfi (Current Pharmaceutical Design, 2022)
Hypothesis: This review article represents a brief layout of the risk factors and pathophysiology responsible for obesity, customary treatment strategies, and nanotechnology-based nutraceutical for the therapeutics of obesity. Experiments: An exhaustive search of the literature was done for this purpose, using Google Scholar, PubMed, and ScienceDirect databases. A literature study was conducted using publications published in peer-reviewed journals between 2000 and 2022. Findings: This was revealed that risk factors responsible for obesity were genetic abnormalities and environmental and socio-economic factors. Several research articles published between 2000 and 2022 were based on phytoconstituents-based nanoformulation for obesity therapeutics and, therefore, have been systematically compiled in this review. Various nutraceuticals like Garcinia cambogia, quercetin, resveratrol, capsaicin, Capsicum, Curcuma longa, Camella Sinensis, Zingiber officinalis, Citrus aurantium, Aegle marmelos, Coffea canephora, Asparagus officinalis, Gardenia jasminoides, Catha edulis, Clusia nemroisa, Rosmarinus officinalis, Cirsium setidens, Betula platyphylla, Tripterygium wilfordi possessing anti-obesity actions are discussed in this review along with their patents, clinical trials as well as their nanoformulation available. Conclusion: This review illustrates that nanotechnology has a great propensity to impart a promising role in delivering phytochemicals and nutraceuticals in managing obesity conditions and other related disorders.
Keywords: nanoformulations